PROMETHEE METHOD FOR DECISION SUPPORT SYSTEM - Andra Andra; Alyauma Hajjah (Journal of Applied Business and Technology, 2020)
The high demand for air conditioners (AC) from year to year has caused an increase the number of AC manufacturers from abroad entering Indonesia market. Here the author will research the PROMETHEE Method for Decision Support Systems. The author will design the application to recommend the best AC where each calculation methods can be tested using the Confusion Matrix Calculation. Confusion Matrix Calculation Results for Â½ PK Air Conditioning PROMETHEE methods where, Recall, Precision, Accuracy are all 100% and Error is 0%.